Improving characteristics of LUT-based Mealy FSMs - Barkalov, Alexander; Titarenko, Larysa; Mielcarek, Kamil (Zielona Góra: Uniwersytet Zielonogórski)
Practically, any digital system includes sequential blocks represented using a model of finite state machine (FSM). It is very important to improve such FSM characteristics as the number of logic elements used, operating frequency and consumed energy. The paper proposes a novel technology-dependent design method targeting a decrease in the number of look-up table (LUT) elements and their levels in logic circuits of FPGA-based Mealy FSMs. It produces FSM circuits having three levels of logic blocks. Also, it produces circuits with regular systems of interconnections between the levels of logic.
Keywords: FPGA; LUT; mealy FSM; structural decomposition; two-fold state assignment; energy consumption